Rituximab combined with Peg-interferon-ribavirin in refractory hepatitis C virus-associated cryoglobulinaemia vasculitis. Issue 10 (4th January 2008) - Saadoun, D; Resche-Rigon, M; Sene, D; Perard, L; Karras, A; Cacoub, P
Abstract : Objectives: To report the results of a pilot study using rituximab combined with Peg-interferon (IFN) α2b-ribavirin in severe refractory hepatitis C virus (HCV) related mixed cryoglobulinaemia (MC) vasculitis. Methods: Sixteen consecutive patients with severe HCV-MC vasculitis that were resistant (n = 11) or relapser (n = 5) to a previous combination treatment with standard (n = 10) or Peg-IFNα2b (n = 6) plus ribavirin were included. They were treated with rituximab (375 mg/m 2 intravenously weekly for 4 weeks) combined with Peg-IFNα2b (1.5 μg/kg per week subcutaneously) plus ribavirin (600–1200 mg/day orally) for 12 months. Results: Fifteen patients (93.7%) showed clinical improvement, 10 of whom (62.5%) were clinical complete responders (CR). HCV RNA and serum cryoglobulin became undetectable in all the clinical CR. Peripheral blood B cell depletion was achieved in all patients (CD19+ cells, 111 (SD 32)/mm 3 at baseline versus 2(2)/mm 3 after the fourth infusion of rituximab) with reconstitution starting at the end of antiviral treatment. Compared with clinical CR, the partial or non-responders had a 3.6 times longer duration of vasculitis prior to treatment and a lower rate of early virological response. Treatment was well tolerated with no infectious complications. After a mean follow-up of 19.4 (SD 3.6) months, two patients experienced clinical relapse associated with a simultaneous reappearance of HCV RNA and cryoglobulin and an increase in the number of B cells. Conclusions: Rituximab combined with Peg-IFNα2b-ribavirin represents a safe and effective treatment option in severe refractory HCV-MC vasculitis.